2021
DOI: 10.1007/s00170-020-06511-3
|View full text |Cite
|
Sign up to set email alerts
|

Induced network-based transfer learning in injection molding for process modelling and optimization with artificial neural networks

Abstract: The necessity of an abundance of training data commonly hinders the broad use of machine learning in the plastics processing industry. Induced network-based transfer learning is used to reduce the necessary amount of injection molding process data for the training of an artificial neural network in order to conduct a data-driven machine parameter optimization for injection molding processes. As base learners, source models for the injection molding process of 59 different parts are fitted to process data. A di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…The authors found that the deep reinforcement learning method outperformed the dispatching rules that are popularly used for minimizing the total weighted tardiness. Another recent study is transfer learning between different injection molding processes to reduce the amount of data needed for model training [17]. The authors used different approaches to ANN models; 16 training samples provided an average R2 value of 0.88 in this paper.…”
Section: Injection Moldingmentioning
confidence: 99%
“…The authors found that the deep reinforcement learning method outperformed the dispatching rules that are popularly used for minimizing the total weighted tardiness. Another recent study is transfer learning between different injection molding processes to reduce the amount of data needed for model training [17]. The authors used different approaches to ANN models; 16 training samples provided an average R2 value of 0.88 in this paper.…”
Section: Injection Moldingmentioning
confidence: 99%
“…To build a neural network model, a multi-layer perceptron (MLP) with a single hidden layer was selected. Lockner and Hopmann suggested that one hidden layer having a single digit number of neurons would be suitable for high model quality for injection molding [ 38 ]. The time and pressure values of the PSPs were inputs to the input layer of the MLP, and the part quality was predicted from the output layer, as shown in Figure 7 .…”
Section: Modeling and Analysismentioning
confidence: 99%
“…However, it is vital to understand that optimization methods that depend exclusively on CAE simulation data are not 100% accurate as they do not fully capture all the physics involved in polymer processing. For that reason, research has been conducted in predicting occurrences within injection molding by developing predictive frameworks [ 18, 19 ] and including real experimental data as training data. For example, Saad Mukras' optimization framework, based on the Kriging Model, predicted cycle time, warpage, and volumetric shrinkage with an error of 6.7%, 3.2%, and 8%, respectively, by analyzing samples from real injection molding trials.…”
Section: Theoretical Backgroundmentioning
confidence: 99%